Muhammadiyah making Indonesia's Islamic moderation based on maqāṣid sharī`ah - Zuly Qodir; Haedar Nashir; Robert W. Hefner (Ijtihad : Jurnal Wacana Hukum Islam dan Kemanusiaan, 2023)
Muhammadiyah, as an Islamic organization together with Nahdatul Ulama, are two Islamic organizations that oversee Islamic moderation in Indonesia. The role of Muhammadiyah in developing the idea of Islamic moderation has been manifested in educational institutions, social services, almsgiving, and health institutions such as Muhammadiyah hospitals. This research used qualitative methods based on manuscripts from journal articles, books, and interviews with expert narrators as material for analyzing the themes studied. This article is based on the theory of maqāṣid sharī`ah put forward by Jasser Auda, which provides a framework for understanding Islamic law based on multidisciplinary obedience and paying attention to the main purpose of Islamic law, not to its legal consequences. The study found that Muhammadiyah, an Islamic organization, is the guardian and propagator of moderate Islam in Indonesian society. Muhammadiyah activities for all citizens have no limits to religion. However, there were considerable obstacles to spreading Islamic moderation by Muhammadiyah. These obstacles come from internal Muslims who consider that Islamic moderation promoted by Muhammadiyah can weaken the Islamic creed of Muslims. They are less familiar with applying maqāṣid sharī`ah in understanding and practicing Islamic law in Indonesia. They are textualists towards the Qur’an and hadith.